A Comparative Analysis of Nurses’ Cultural Competence in Inpatient, Outpatient, and Emergency Rooms within Hospital Setting - Azizah Abdullah, Syamsiah Nur; Asmaningrum, Nurfika; Nur, Kholid Rosyidi Muhammad (jitek, 2022)
Cultural diversity affects individual beliefs and understanding of treatment situations, influencing the treatment process. As care providers, nurses must deliver culturally sensitive care, so cultural competence is paramount. Cultural competence is a crucial element of cross-cultural care. Nevertheless, research on assessing nurses’ cultural competence across different care settings is lacking. This study was aimed to analyze differences in nurses’ cultural competence in inpatient, outpatient, and emergency rooms. The study used a non-experimental quantitative design with a cross-sectional approach conducted on 108 nurses in inpatient, outpatient, and emergency rooms. Data were collected using a Cultural Competence Assessment Instrument (CCAI) questionnaire. The data analysis used univariate and bivariate analysis. Descriptive analysis and the Kruskal Wallis test were used to analyze the data, with p<0.05. The analysis results documented no significant difference in cultural competence among the nurses, evidenced by p 0.841. Their cultural competence was not significantly related to the type of nursing service provided. However, cultural competence is dependent on nurses’ cultural knowledge and organizational support related to the provision of cultural competence training.